2000
DOI: 10.1007/s11746-000-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipase activity and fatty acid typoselectivities of plant extracts in hydrolysis and interesterification

Abstract: Lipase fatty acid typoselectivities of Euphorbia characias latex and commercially available crude preparation of bromelain were determined in the hydrolysis of homogeneous triacylglycerols (TAG) and natural TAG mixtures. Their activities were compared to a commercially available crude preparation of papain. Under optimal lipolysis conditions at pH 8.0 and 10 min of incubation time, maximal activities were observed at 45, 55, and 50°C, respectively, for E. characias latex, crude bromelain, and crude papain. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
10

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 11 publications
5
26
0
10
Order By: Relevance
“…However, several studies have indicated that such processes are very expensive due to the high cost of purifying the microbial enzymes (de Castro et al, 2004;Noor et al, 2003). Seed lipases present certain advantages since they do not necessarily have to be purified in order to perform this and other processes (Caro et al, 2000). A partially purified raw extract of Nigella sativa L. was used by Tuter et al (2003) as a lipase source for enriching borage oil with gamma-linolenic fatty acid, obtaining 34.6% incorporation.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…However, several studies have indicated that such processes are very expensive due to the high cost of purifying the microbial enzymes (de Castro et al, 2004;Noor et al, 2003). Seed lipases present certain advantages since they do not necessarily have to be purified in order to perform this and other processes (Caro et al, 2000). A partially purified raw extract of Nigella sativa L. was used by Tuter et al (2003) as a lipase source for enriching borage oil with gamma-linolenic fatty acid, obtaining 34.6% incorporation.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…Nevertheless, it is recommended to work at 55°C for industrial consideration (lower energy cost). In aqueous medium, the optimal temperature for the C. papaya lipase catalyzed hydrolysis of tributyrin was about 50°C but its hydrolytic activity decreased after 10 min reaction at 55°C [18]. Furthermore, the yields of the esterification and transesterification reactions as a function of the temperature were comparable despite water being produced in the former reaction but not the latter ( figure 3).…”
Section: Effect Of the Temperature On Esterification And Transesterifmentioning
confidence: 97%
“…In contrast, the optimal activity temperature for bacterial lipases is between 37°C and 65°C with a majority being at 50-65°C [10,11]. Over the past few years, a large body of work has been reported on reactions catalyzed by plant lipases [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. From an industrial viewpoint, crude plant extracts are readily available and generally are low cost materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta enzima foi caracterizada em reação de hidrólise como tipo-seletiva para triacilgliceróis de cadeias curtas, com máxima atividade para a tributirina (1590 +/-33 UI/g) entre triacilgliceróis homogê-neos de 2 a 18 carbonos 26,27 e óleos naturais (oliva, linhaça, copra e girassol -Figura 3) 27 . A temperatura ótima da hidrólise foi de 55 ºC (pH 8,0) e a energia de ativação de Arrhenius foi de 24 Kcal/mol 26 .…”
Section: Caracterização E Aplicações Em Reação De Hidróliseunclassified